THE PROBLEM OF UNDERSTANDING OTHERS AND SELF-UNDERSTANDING IN CONFLICT SITUATIONS (IN THE CONTEXT OF STUDENT–TEACHER RELATIONSHIPS) (Global Conference on Multidisciplinary Research and Innovation, 2026)
This article examines the problem of understanding others and self-understanding in conflict situations within the context of student–teacher relationships. The study analyzes the psychological and pedagogical factors that influence mutual understanding between students and teachers, particularly in situations where disagreements or conflicts arise during the educational process. Special attention is given to the role of empathy, communication skills, emotional intelligence, and reflective thinking in resolving conflicts and improving interpersonal interaction in the classroom. The article highlights that effective self-understanding and the ability to understand others contribute to the development of constructive dialogue, mutual respect, and a positive learning environment. The research emphasizes the importance of pedagogical strategies aimed at strengthening communicative competence and conflict resolution skills among both teachers and students.
Keywords: self-understanding, understanding others, conflict situations, student–teacher relationships, interpersonal communication, empathy, emotional intelligence, conflict resolution, educational environment, pedagogical interaction.